Singing together or apart: the effect of competitive and cooperative singing on social bonding within and between sub-groups of a university fraternity - Pearce, E; Launay, J; Duijin, M; Rotkirch, A; David-Barrett, T; Dunbar, R (SAGE Publications, 2016)
Singing together seems to facilitate social bonding, but it is unclear whether this is true in all contexts. Here we examine the social bonding outcomes of naturalistic singing behaviour in a European university Fraternity composed of exclusive “Cliques”: recognised sub-groups of 5–20 friends who adopt a special name and identity. Singing occurs frequently in this Fraternity, both “competitively” (contests between Cliques) and “cooperatively” (multiple Cliques singing together). Both situations were recreated experimentally in order to explore how competitive and cooperative singing affects feelings of closeness towards others. Participants were assigned to teams of four and were asked to sing together with another team either from the same Clique or from a different Clique. Participants (N = 88) felt significantly closer to teams from different Cliques after singing with them compared to before, regardless of whether they cooperated with (singing loudly together) or competed against (trying to singing louder than) the other team. In contrast, participants reported reduced closeness with other teams from their own Clique after competing with them. These results indicate that group singing can increase closeness to less familiar individuals regardless of whether they share a common motivation, but that singing competitively may reduce closeness within a very tight-knit group.